โมเดลเชิงสาเหตุการมีส่วนร่วมของแม่ในโปรแกรมการสร้างเสริมพัฒนาการระยะแรกเริ่มในเด็กที่มีความต้องการพิเศษ - เพิ่มพูน สานิชวรรณกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The purposes of this study were 1) to validate the causal model of maternal involvement in early intervention programs for children with special needs aged 0-6 years with the empirical data 2) to study the pattern of direct and indirect effects of factors associated with maternal involvement in early intervention programs for children with special needs. Participants were 343 mothers of children with special needs aged 0-6 years who were receiving early intervention service at the hospitals or early intervention centers in Bangkok and upcountry. The model consisted of 5 latent variables measured by 12 observable variables namely; socio-economic status (2 variables), social support (3 variables), stress (2 variables), coping (3 variables), and maternal involvement (2 variables). Data were collected by questionnaires and analyzed by LISREL 8.72 program. Structural equation modeling analyses indicated that the causal model was significantly well consistent with empirical data as indicated by X² = 29.21, df = 20, p = .084, RMSEA = .037, standardized RMR = .058, GFI = .986, and AGFI = .945. Independent variables in the model accounted for 30 percent variance in maternal involvement. The causal model indicated that 1) Socio-economic status had both direct and indirect effects on maternal involvement through stress. 2) Social support had a direct effect on maternal involvement. 3) Stress had both direct and indirect effects on maternal involvement through coping. 4) Coping had a direct effect on maternal involvement. Results suggested that low income and level of education were associated with increased stress and decreased maternal involvement. High levels of maternal social supports were related to high level of maternal involvement. However, social support did not have influence on stress and coping. Moreover, mothers who reported high stress would utilize high coping. Maternal coping was linked to 3 styles of coping namely; high problem coping, very high emotion coping, and low avoidance coping. No matter what any styles of coping were used, mothers were likely to involve in early intervention programs for children.